A medical history of Pulau Pinang, 1900-1957, with special attention to Malaria, Tuberculosis and Leprosy / Lee J. Peter - Lee, J. Peter (2017)
This study has been analysed against the broad historical framework of British Colonial Administration period from 1900-1957. The purpose of this research is to examine the medical history in the state of Pulau Pinang, which consist of Penang Island and Seberang Perai. This research will focus mainly on three infectious diseases, namely malaria, tuberculosis and leprosy during the British Colonial Administration period. This research defines the role of the British Colonial Administration and the Department of Health in providing healthcare services and helping to resolve problems caused by infectious diseases, mainly malaria, tuberculosis and leprosy in Pulau Pinang during that period. This study uses the historical research method. The discussion in the thesis will be based on qualitative research in which a thematic and descriptive/analytical approach will be used. For primary data, all data that compatible with this study was assimilated with the other primary data to form a new stronger fact. Secondary resources used as support to the existing data after selecting the compatible secondary material. This research shows that the British Colonial Administration faced many challenges in the prevention, treatment and cure of infectious diseases such as malaria, tuberculosis and leprosy in Pulau Pinang from 1900 to 1957. Despite this, the Colonial Government reduced the death rates and cured the patients who were affected by those diseases. This success was attributed to the good working relationship and coordination that existed between the Colonial Government, the local authorities and the non-profit organisations which helped towards the prevention and eradication of these diseases in Pulau Pinang.